Measuring Social Media Functionality on the Formation of Tourist Value Creation - Moussa Elsamadicy, Ahmed (British Journal of Marketing Studies, 2020)
This study seeks to measure the factors related to social media functionality in the tourism industry promotion and its impact on the formation of Tourist Value Creation. This study hypothesized that media presence, information sharing, relational bonds, conversation, and reputation impact in tourist value creation (influence tourist planning/ taking trips). This study uses a quantitative research approach, with a cross-sectional design and a descriptive purpose. Each of the variables is measured using a 5-point Likert scale (the number of the items varied in each scale). This study distributed questionnaires online, using non-probability sample. The SPSS program is used to analyze the collected data. Based on this study’s outcome, all the hypotheses were supported except for one hypothesis. Social media functionality related to conversation development, information sharing, online presence, and reputation impact tourist value creation. Relationship building through social media was deemed insignificant. This study seeks to provide noncommercial accumulated and up-to-date knowledge in the discipline. Industry practitioners can apply the empirical findings from this academic research to their businesses in order to remain competitive.